RATIO LEGIS DAN PROBLEMATIKA PENERAPAN UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI SEBAGAI UPAYA PEMULIHAN KERUGIAN NEGARA - Neng Erna Sry Denasty (Universitas Labuhanbatu, 2025)
A criminal corruption verdict not only imposes a basic punishment in the form of imprisonment and fines, but also imposes an additional punishment in the form of compensation with subsidiary punishment for who are unable to pay the compensation. This study aims to analyze the implementation of subsidiary punishment for compensation payments in corruption cases in Indonesia and to develop a concept of the ratio legis for subsidiary compensation payments for the recovery of state losses. The research method used is normative juridical which use the law as stated in legislation (law in books) descriptively by providing an overview and analysis of the implementation of legislative provisions based on applicable legal provisions in relation to legal theory and the practice of positive law. Based on the results of the research that subsidiary punishment compensation has not been effective, as evidenced by the emergence of various issues in court rulings. The ratio legis of subsidiary compensation payments is based on the absence of guidelines for imposing subsidiary penalties, which leads to disparities in verdicts and imbalances between the amount of compensation and subsidiary penalties. This weak concept causes problems in law enforcement, particularly in relation to the effectiveness of the implementation and execution of compensation payments. The original contribution of this research lies in the use of ratio legis as the basis for drafting new guidelines for imposing subsidiary punishment in corruption crimes who approach offers a normative solution in the form of guidelines that are more proportional, consistent with substantive justice, legal certainty, and the effectiveness of corruption eradication.Keywords: State Losses; Corruption; Subsidiary Punishment.